2007
DOI: 10.1136/gut.2006.096842
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic gastroplication for the treatment of gastro-oesophageal reflux disease: a randomised, sham-controlled trial

Abstract: Background: Endoscopic treatment for gastro-oesophageal reflux disease (GORD) is rapidly emerging, but there is a great need for randomised controlled trials to evaluate the efficacy. Design and setting: A single-centre, double-blind, randomised, sham-controlled trial of endoscopic gastroplication by the Endocinch suturing system. Patients and interventions: 60 patients with GORD were randomly assigned to three endoscopic gastroplications (n = 20), a sham procedure (n = 20) or observation (n = 20). The researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
81
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(86 citation statements)
references
References 23 publications
(21 reference statements)
2
81
1
2
Order By: Relevance
“…After 1 year, a sustained significant improvement in symptom scoring, regurgitation, and quality of life and a reduction in the requirement of PPIs have been reported [43]. Schwartz et al [48] recently reported the first EndoCinch sham-controlled trial. The results of this trial confirm those of prior open-label studies [43, 44, 49], showing that in the short and intermediate terms, endoscopic gastroplication improves GORD symptoms and quality of life and reduces the requirements of acid-inhibitory drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 1 year, a sustained significant improvement in symptom scoring, regurgitation, and quality of life and a reduction in the requirement of PPIs have been reported [43]. Schwartz et al [48] recently reported the first EndoCinch sham-controlled trial. The results of this trial confirm those of prior open-label studies [43, 44, 49], showing that in the short and intermediate terms, endoscopic gastroplication improves GORD symptoms and quality of life and reduces the requirements of acid-inhibitory drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In the sham-controlled study reported by Schwartz et al [48], endoscopy/gastroplication was performed only in patients of the active treatment group who had treatment failure, and hence the actual proportion of patients who have retention of stitches (or judged to be functional) is unknown in this group. However, retention of stitches seems to be a major problem reported with this technique [48, 52, 53]. Further studies are needed to confirm the above.…”
Section: Discussionmentioning
confidence: 99%
“…Less-invasive endoscopic suturing devices as the Endocinch (Bard Endoscopic Technologies, Nurray Hill, NJ, USA), Plicator (NDO Surgical Inc., Mansfield, MA, USA) and the EsophyX (EndoGastric Solutions, Inc., Silver Spring, MD, USA) have tried to mimic the effects of conventional anti-reflux surgery by the creation of gastroesophageal plications. [29][30][31] Although early improvements in symptoms and medication use were reported in several trials, clinical efficacy or durability to the level of conventional anti-reflux surgery have not been met. 32 The Enteryx procedure aimed to increase sphincter competence by injection of sponge-like material into the LES.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, 18 patients have completed 3-month follow-up and 14 patients 6-month follow-up. Interim results showed a positive ef- fect on symptoms: GERD-HRQL median (IQR) score was 4 (2-11) at 3 months and 5 (4-9) at 6 months, respectively with P < 0.001 and P < 0.01 when compared to baseline score off PPI (31 [25][26][27][28][29][30][31][32][33][34][35][36][37]). Furthermore, acid exposure time decreased from 11.3% (9.0-15.5%) at baseline to 3.3% (2.5-9.1%) at 3 months and to 2.6% (1.8-5.4%) at 6 months (Fig.…”
mentioning
confidence: 99%
“…Bard, Murray Hill, NJ), was first described in the context of treating gastroesophageal reflux disease. Due to lack of repair durability, the role of EVG in control of gastroesophageal reflux disease (GERD) was abandoned [25][26][27] . In terms of its application for the treatment of obesity, Fogel et al [28] first described the use of the EndoCinch in 64 patients.…”
Section: Endoluminal Suturingmentioning
confidence: 99%